Immune Escape Strategies of Malaria Parasites - Gomes, Pollyanna S.; Bhardwaj, Jyoti; Rivera-Correa, Juan; Freire-De-Lima, Celio G.; Morrot, Alexandre (Frontiers in Microbiology, 2016)
Malaria is one of the most life-threatening infectious diseases worldwide. Immunity to malaria is slow and short-lived despite the repeated parasite exposure in endemic areas. Malaria parasites have evolved refined machinery to evade the immune system based on a range of genetic changes that include allelic variation, biomolecular exposure of proteins and intracellular replication. All of these features increase the probability of survival in both mosquitoes and the vertebrate host. Plasmodium species escape from the first immunological trap in its invertebrate vector host, the Anopheles mosquitoes. The parasites have to pass through various immunological barriers within the mosquito such as anti-microbial molecules and the mosquito microbiota in order to achieve successful transmission to the vertebrate host. Within these hosts, Plasmodium species employ various immune evasion strategies during different life cycle stages. Parasite persistence against the vertebrate immune response depends on the balance among virulence factors, pathology, metabolic cost of the host immune response, and the parasites ability to evade the immune response. In this review we discuss the strategies that Plasmodium parasites use to avoid the vertebrate host immune system and how they promote successful infection and transmission.